ANALYSIS OF THE OPERATION MODE OF THE SYNCHRONOUS COMPENSATOR (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The main consumers of electrical energy, in addition to active power, consume reactive power from the generators of the system. Consumers requiring large magnetizing reactive currents to create and maintain magnetic flux include induction motors, transformers, induction furnaces, and others. As a result, distribution networks usually operate with lagging current.